Wideband Circularly Polarized Microstrip-Slot Antenna with Parasitic Ground Planes - Qin Huang (International Journal of Antennas and Propagation)
In this study, a new stacked microstrip slot antenna (MSA) with wideband circular polarization (CP) characteristics is proposed. The antenna consists of a square-loop feed configuration, four parasitic square patches, four parasitic vertical planes, and a square ground plane etched with four parasitic square slots. The corner-cut square-loop can excite a stable 270° phase difference by loading an arc-shaped strip into the square-loop. Square-patches, vertical planes, and square slots as parasitic elements are placed together at the side of the square-loop to stimulate two CP resonant points. Simulation and measurement are performed on the designed antenna prototype to demonstrate the design’s rationality. The measured results depict that the measured impedance bandwidth (IBW) for |S11| < −10 dB is 36.4% (4.65 to 6.70 GHz) and the measured axial ratio bandwidth (ARBW) for AR < 3 dB is 25.1% (5.01 to 6.45 GHz). Compared with other reported stacked CP antennas, the proposed antenna has significant advantages in CP bandwidth, which could occupy the wireless local area network ITS (5.8 GHz), (5.725–5.85 GHz), and WIFI (5.85–5.925 GHz) bands.